Aesthetics of artistic portrayal of the conditions of the unbelievers in the Holy Quran - Saki, Dr. Nancy; Ajrash, Dr. Khairiya; Al-Rikabi, Esraa Shiaa Mohsen Obaid (Thi Qar Arts Journal, 2022)
Artistic depiction is considered one of the most important and wonderful methods of presenting the external and internal concepts, which the Qur’an used extensively in its various types of speeches with people, believers and disbelievers, and to explain their worldly and hereafter conditions, as they include strong indications and deep explanations of the divine will, and one of these conditions is the state of the unbeliever in the Hereafter. And the cases, fluctuations, discourses, and observations that befall him, and the Qur’an abounds in explaining their cases by means, including their artistic depiction, in order to have a stronger influence on the addressees, especially the obstinate and unbelievers, and turn them around, and if possible, guide them and bring them back to the truth. But what is artistic depiction, and how did the Qur’an employ this art in demarcating and depicting the conditions of the disbelievers in the afterlife? In this article, which will be written on a descriptive-analytical approach and also on a library, the researchers will search for the meaning of the term artistic depiction, its elements, and its importance in clarifying the meaning and its impact, and after mentioning the models of its employment for the afterlife conditions of the infidels. In other words, the metaphor works with the function of anthropomorphism, diagnosis, and representation, in a wonderful way to explain the conditions of the infidels of regret, pain, deprivation, amazement, disappointment, and the like. Keywords: